Legume-Grass Intercropping in Indonesian Pastures: A Systematic Review on Soil and Forage Nutritional Improvements - Ohiwal, Morgan; Teele, Tshepo; Garfansa, Marchel Putra (Environmental and Agriculture Management, 2025)
The productivity and quality enhancement of tropical pastures in Indonesia faces critical constraints from soil degradation and low forage nutritional value. This study evaluates the potential of legume cover crop integration to simultaneously improve grass biomass, forage quality, and soil physicochemical properties. Through comprehensive analysis of 42 peer-reviewed articles from Scopus, Web of Science, and Google Scholar, we demonstrate the multifunctional benefits of legume-grass systems across Indonesia's diverse agroecosystems. Research findings reveal consistent improvements in both productivity and soil health parameters. Legume integration enhances biomass production by 30-65% and elevates crude protein content by 40-50% compared to conventional grass monocultures. Particularly effective species such as Leucaena leucocephala and Centrosema pubescens contribute to measurable soil quality enhancements, including increased organic matter content (0.5-1.5%), improved cation exchange capacity (2-5 cmol(+)/kg), and superior water retention capacity (15-20% improvement), while concurrently reducing soil erosion rates. Despite these demonstrated benefits, practical implementation faces several challenges. Rhizobia inoculation requirements present technical barriers for some farming communities, while species-specific soil adaptation needs necessitate careful selection of appropriate legume varieties. Economic constraints further complicate adoption among smallholder farmers, particularly in resource-limited settings. This study underscores legume integration as a sustainable intensification strategy for tropical pasture systems. The findings hold significant implications for developing sustainable livestock policies in Indonesia, offering pathways to reduce chemical fertilizer dependence while simultaneously addressing food security concerns and improving smallholder livelihoods. The dual benefits of productivity enhancement and environmental conservation position legume-based systems as a climate-smart agricultural approach for Indonesia's pasturelands.